Electrodeposition of Tin-Bismuth Alloys: Additives, Morphologies and Compositions. Issue 2 (11th January 2018) - Rajamani, A. R.; Jothi, Sathiskumar; Datta, Madhav; Rangarajan, Murali
Abstract : Electrodeposition of tin-bismuth alloys on polycrystalline copper electrodes has been studied from an acidic bath comprising SnCl4, Bi(NO3 )3, citric acid, poly(vinyl alcohol) and betaine. Using linear sweep voltammetry (LSV) and chronoamperometry (CA), co-deposition of tin and bismuth from the above bath has been examined. Bismuth (III) ions get reduced in a single-step, three-electron-transfer reaction while tin (IV) ions undergo a two-step reduction through the formation of tin (II) ions. Nitric acid in the bath not only enhances solubility of the precursors but also decreases the peak potential separation between bismuth (III) and tin (II) ions. Through the introduction of various additives and variation in bath pH, co-deposition is preserved while the composition of tin in the obtained alloy is modified. The morphologies, composition and crystallinity of the deposits have been determined using scanning electron microscopy, inductively coupled plasma atomic emission spectroscopy and X-ray diffraction, respectively. A wide range of alloy compositions (from 14% to 75% tin), including the eutectic Sn-Bi alloy have been deposited. Novel morphologies such as yarns-of-spool have been obtained.